¿Las redes virtuales de aprendizaje son mediadoras en la construcción de conocimiento escolar?, revisión de algunos antecedentes de investigación - Molina Vásquez, Ruth (Revista Científica, 2011)
From reflection about how the virtual networks learning-RVA-, qualify processes of learning in the school, this paper presents some elements of research projects,that have inquired about this topic. It uses the methodology of documentary analysis, to categorize the issues that guide these researchs, its objectives, methodologies, theories and conclusions. From these researchs, this papers presents a brief reflection about the possibilities by these these networks as mediators offer in the processes of construction of school knowledge.